Epoxy resin composition, molding material for fiber-reinforced composite material, and fiber-reinforced composite material
The epoxy resin composition with controlled components and dispersants addresses uneven curing and solvent residue issues, resulting in improved mechanical characteristics and appearance in fiber-enhanced composite materials.
Patent Information
- Application Number
- JP2021505430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-01-27
AI Technical Summary
Conventional methods for distributing solid curing agents in epoxy resin compositions for fiber-enhanced composite materials result in uneven mechanical characteristics and surface imperfections due to solvent residue and incomplete curing, particularly in thick sheets like SMC.
An epoxy resin composition containing specific components (a) with two or more epoxy groups, (b) solid curing agents, and (c) dispersing agents, with controlled viscosity and particle size, ensuring uniform distribution and impregnation of the curing agents into reinforced fibers.
The composition achieves improved mechanical characteristics and reduced unevenness in the composite materials, with enhanced impregnation and better appearance, suitable for aerospace, automotive, and industrial applications.
Smart Images

Figure 0007622627000001 
Figure 0007622627000002 
Figure 0007622627000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an epoxy resin composition that is suitably used for fiber-reinforced composite materials such as aerospace parts and automotive parts, and to a molding material for fiber-reinforced composite materials and fiber-reinforced composite materials each using the same. [Background technology]
[0002] Fiber-reinforced composite materials, which are made of reinforcing fibers and a matrix resin, can be designed to take advantage of the advantages of both the reinforcing fibers and the matrix resin, and their applications are expanding to include aerospace, sports, and general industrial fields.
[0003] Fiber-reinforced composite materials, which consist of reinforcing fibers and matrix resins, can be designed to take advantage of the advantages of the reinforcing fibers and matrix resins, and so their applications are expanding to the aerospace and automotive fields as well as the sports and general industrial fields, etc. Fiber-reinforced composite materials are manufactured by the hand layup method, the filament winding method, the pultrusion method, the resin transfer molding (RTM) method, the autoclave molding method of prepregs, and the press molding method of molding materials for fiber-reinforced composite materials.
[0004] Examples of molding materials for fiber-reinforced composites used in the press molding method include prepregs, towpregs, bulk molding compounds (BMC), sheet molding compounds (SMC), etc. These molding materials for fiber-reinforced composites are made by impregnating reinforcing fibers with a matrix resin.
[0005] Examples of the reinforcing fibers include glass fibers, aramid fibers, carbon fibers, and boron fibers. As the matrix resin, both thermosetting and thermoplastic resins are used, but thermosetting resins that are easy to impregnate into the reinforcing fibers are often used. Examples of the thermosetting resins that can be used include epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, bismaleimide resins, and cyanate resins. Among these, epoxy resins are widely used from the viewpoints of adhesion to the reinforcing fibers, dimensional stability, and mechanical properties such as the strength and rigidity of the resulting fiber-reinforced composite material.
[0006] When epoxy resin compositions or molding materials for fiber-reinforced composite materials such as prepregs are stored at room temperature for a long period of time, unintended curing reactions proceed, so solid curing agents that are solid at room temperature are used from the viewpoint of storage stability. However, when a solid curing agent is used, the viscosity of the resin at room temperature increases, the impregnation of the reinforcing fibers decreases, and the matrix resin does not sufficiently penetrate into the reinforcing fiber bundles. In order to fully exhibit the excellent mechanical properties of the reinforcing fibers, it is necessary to reduce the viscosity of the resin. In response to this situation, a method of impregnating reinforcing fibers with a matrix resin solution diluted with a solvent has been disclosed (Patent Document 1).
[0007] In addition, the solid curing agent aggregates in the matrix resin, reducing the amount of curing agent in the reinforcing fiber bundle, causing the curing reaction to be partially incomplete and resulting in uneven mechanical properties. Furthermore, the curing agent that does not penetrate into the reinforcing fibers accumulates on the reinforcing fibers and impairs the surface appearance, so it is necessary to uniformly disperse the solid curing agent in the matrix resin. In response to this situation, a method has been disclosed in which the solid curing agent is uniformly dissolved in a solvent such as dimethylformamide beforehand and then used as a method for uniformly mixing the solid curing agent (Patent Document 2). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2003-213015 A [Patent Document 2] Japanese Patent Application Publication No. 2-286722 Summary of the Invention [Problem to be solved by the invention]
[0009] The method described in Patent Document 1 can be applied to molding materials for thin fiber-reinforced composites, such as prepregs, from which the solvent can be easily removed. However, it is difficult to remove the solvent from thick sheets such as SMC, and the solvent remains inside, which creates voids during molding and causes unevenness in the mechanical properties of the resulting fiber-reinforced composite material.
[0010] According to the method described in Patent Document 2, the solid curing agent can be uniformly dispersed in the matrix resin by dissolving the solid curing agent uniformly in a solvent such as dimethylformamide in advance. However, there is a problem that the solvent remains inside, which generates voids during molding and causes unevenness in the mechanical properties of the obtained fiber-reinforced composite material.
[0011] Thus, in the prior art, there was no technology capable of uniformly dispersing a solid curing agent in a matrix resin while maintaining good impregnation into reinforcing fibers. Therefore, an object of the present invention is to improve the drawbacks of the prior art and provide an epoxy resin composition excellent in dispersibility of a solid curing agent and impregnation into reinforcing fibers, to provide a molding material for a fiber-reinforced composite material excellent in dispersibility of a solid curing agent in a resin after thickening by using the epoxy resin composition, and to provide a fiber-reinforced composite material excellent in appearance quality and mechanical properties and less unevenness in physical properties by using the molding material for a fiber-reinforced composite material. [Means for solving the problem]
[0012] In order to solve the above problems, the epoxy resin composition of the present invention is an epoxy resin composition containing all of the following components (A) to (C), wherein the dispersity of component (B) in component (A) is 0.1 to 0.8, the viscosity at 25°C is 0.1 to 100 Pa s, and the glass transition temperature of the cured epoxy resin material at a cure degree of 85 to 95% is 110°C or higher. Component (A): Epoxy resin with two or more epoxy groups in one molecule Component (B): Solid hardener Component (C): A dispersant that is compatible with component (A).
[0013] The molding material for a fiber-reinforced composite material of the present invention is a molding material for a fiber-reinforced composite material comprising a thickened resin and reinforcing fibers, and the thickened resin is the epoxy resin composition of the present invention in a semi-cured state. Furthermore, the fiber-reinforced composite material of the present invention is obtained by molding the molding material for a fiber-reinforced composite material of the present invention. Effect of the Invention
[0014] The epoxy resin composition of the present invention is superior in dispersibility of the solid curing agent and in impregnation into reinforcing fibers compared to conventional epoxy resin compositions, and therefore can provide a molding material for a fiber-reinforced composite material having excellent dispersibility of the solid curing agent in the thickened resin. Furthermore, by using such a molding material for a fiber-reinforced composite material, a fiber-reinforced composite material having excellent appearance quality and mechanical properties and little unevenness in physical properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Preferred embodiments of the present invention will be described below. First, the epoxy resin composition according to the present invention will be described.
[0016] The epoxy resin composition of the present invention contains component (A): an epoxy resin having two or more epoxy groups in one molecule. Component (A) is a component necessary for exhibiting heat resistance and mechanical properties. Specific examples of component (A) include epoxy resins having two epoxy groups such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, and epoxy resins modified from these. Examples of epoxy resins having three or more epoxy groups include, but are not limited to, aliphatic epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, cresol type epoxy resins, glycidylamine type epoxy resins such as tetraglycidyldiaminodiphenylmethane, triglycidylaminophenol, and tetraglycidylamine, glycidyl ether type epoxy resins such as tetrakis(glycidyloxyphenyl)ethane and tris(glycidyloxymethane), and epoxy resins modified from these and brominated epoxy resins obtained by brominating these epoxy resins. Two or more of these epoxy resins may also be used in combination.
[0017] Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, and cresol novolac type epoxy resin are particularly suitable. The use of these epoxy resins provides an additional effect of improving the mechanical properties when made into a fiber-reinforced composite material, compared to the use of highly rigid epoxy resins such as epoxy resins having a naphthalene skeleton in one molecule. This is presumably because highly rigid epoxy resins tend to be distorted when cured in a short time due to an increase in crosslink density, whereas the use of the above-mentioned epoxy resins reduces the possibility of such problems occurring.
[0018] Commercially available aliphatic epoxy resins include "Denacol (registered trademark)" EX-313, EX-314, EX-321, EX-411, EX-421, EX-512, EX-521, EX-611, EX-612, EX-614, EX-614B, and EX-622 (all manufactured by Nagase ChemteX Corporation). Commercially available bisphenol A type epoxy resins include jER (registered trademark) 825, jER (registered trademark) 826, jER (registered trademark) 827, jER (registered trademark) 828, jER (registered trademark) 834, jER (registered trademark) 1001, jER (registered trademark) 1002, and jER (registered trademark) 1003 (all manufactured by Mitsubishi Chemical Corporation), Epicron (registered trademark) 850 (manufactured by DIC Corporation), Epotohto (registered trademark) YD-128, YD-128G, and YD-128S (manufactured by Nippon Steel Chemical & Material Co., Ltd.), and DER (registered trademark) -331 (manufactured by Dow Plastics).
[0019] Commercially available bisphenol F type epoxy resins include jER (registered trademark) 806, jER (registered trademark) 807, jER (registered trademark) 1750, Epicron (registered trademark) 830 (manufactured by DIC Corporation), Epotohto (registered trademark) YDF-170, and Epotohto (registered trademark) YDF2001. Commercially available alkyl-substituted tetramethylbisphenol F type epoxy resins include Epotohto (registered trademark) YSLV-80Y / X (Nippon Steel Sumikin Chemical Co., Ltd.).
[0020] An example of the bisphenol S type epoxy resin is "Epiclon (registered trademark)" EXA-1515 (manufactured by DIC Corporation).
[0021] Commercially available phenol novolac epoxy resins include jER (registered trademark) 152 and jER (registered trademark) 154 (all manufactured by Mitsubishi Chemical Corporation), Epicron (registered trademark) N-740, Epicron (registered trademark) N-770, and Epicron (registered trademark) N-775 (all manufactured by DIC Corporation).
[0022] Commercially available cresol novolac epoxy resins include "Epicron (registered trademark)" N-660, "Epicron (registered trademark)" N-665, "Epicron (registered trademark)" N-670, "Epicron (registered trademark)" N-673, "Epicron (registered trademark)" N-695 (all manufactured by DIC Corporation), EOCN-1020, EOCN-102S, EOCN-104S (all manufactured by Nippon Kayaku Co., Ltd.), and the like.
[0023] The epoxy resin composition of the present invention comprises a component (B): a solid curing agent. Component (B) is a curing agent for component (A) and is in a solid state at 25°C.
[0024] There are no particular limitations on component (B) so long as it is a curing agent that is in a solid state at 25° C., but it is preferable for it to be an aromatic amine curing agent, dicyandiamide or a derivative thereof. The aromatic amine curing agent is not particularly limited as long as it is an aromatic amine used as an epoxy resin curing agent. Specific examples of the aromatic amine curing agent include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 4,4'-diaminodiphenyl sulfone (4,4'-DDS), diaminodiphenylmethane (DDM), 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3, Examples of the 2-ethylhexanoic acid ester of 2,4,6-tris(dimethylaminomethyl)phenol include 3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether (DADPE), bisaniline, benzyldimethylaniline, 2-(dimethylaminomethyl)phenol (DMP-10), 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30), and the like. These may be used alone or in combination of two or more.
[0025] Commercially available aromatic amine curing agents include Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.), MDA-220 (manufactured by Mitsui Chemicals, Inc.), "jER Cure (registered trademark)" W (manufactured by Japan Epoxy Resins Co., Ltd.), and 3,3'-DAS (manufactured by Mitsui Chemicals, Inc.), "Lonzacure (registered trademark)" M-DEA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-DIPA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-MIPA (manufactured by Lonza Corporation), and "Lonzacure (registered trademark)" DETDA 80 (manufactured by Lonza Corporation).
[0026] Commercially available dicyandiamide products include "jER Cure (registered trademark)" DICY7, "jER Cure (registered trademark)" DICY15, "jER Cure (registered trademark)" DICY50 (all manufactured by Mitsubishi Chemical Corporation), "DYHARD (registered trademark)" 100, "DYHARD (registered trademark)" 100S, "DYHARD (registered trademark)" 100SF (all manufactured by AlzChem), "Amicure (registered trademark)" Cg-325G, "Amicure (registered trademark)" CG-1200G, "Dicyanex (registered trademark)" 1400F (all manufactured by EVONIK), and the like.
[0027] From the viewpoint of heat resistance and mechanical properties, the content of component (B) is preferably 1 to 50 parts by mass, more preferably 2 to 50 parts by mass, and even more preferably 3 to 25 parts by mass, relative to 100 parts by mass of component (A). When the content of component (B) is 1 part by mass or more, a sufficient effect of improving curability is easily obtained. In addition, when the content of component (B) is 50 parts by mass or less, the epoxy resin cured product obtained by curing the epoxy resin composition is likely to have higher heat resistance.
[0028] The average particle diameter of component (B) is preferably 0.5 to 50 μm. The upper limit of the average particle diameter is more preferably 25 μm, further preferably 10 μm, and most preferably 3 μm. The average particle diameter of component (B) in the present invention is the arithmetic mean value of the average particle diameters of each particle extracted in an observation image observed by an observation means such as an optical microscope or an electron microscope. The average particle diameter of each particle is calculated as the average of the diameters connecting two points on the periphery of each particle and passing through the center of gravity. In the present invention, the average particle diameter of (B) is calculated from the average particle diameter of each particle and its average value using the image processing software "Image Pro Premier 3D 64-bit Ver 9.2" manufactured by Media Cybernetics from the dispersion image obtained by an observation means such as an optical microscope or an electron microscope. If the average particle diameter of component (B) is 50 μm or less, for example, when used for prepreg applications, component (B) is likely to enter the carbon fiber bundle when the resin composition is impregnated into the carbon fiber bundle by heating and pressurizing, and is unlikely to be left behind on the surface layer of the carbon fiber bundle.
[0029] From the viewpoints of long-term storage stability at room temperature and viscosity stability during prepregging, it is preferable that component (B) is dicyandiamide or a derivative thereof.
[0030] Examples of curing agents other than those described above include amines such as alicyclic amines, phenolic compounds, acid anhydrides, polyaminoamides, organic acid hydrazides, isocyanates, etc. These curing agents may be used in combination with aromatic amine curing agents, dicyandiamide or derivatives thereof.
[0031] The epoxy resin composition of the present invention contains component (C): a dispersant compatible with component (A). Component (C) has the effect of uniformly dispersing component (B) in component (A). Specific examples of component (C) include surfactants, high molecular weight dispersants, ionic liquids, etc.
[0032] From the viewpoint of compatibility with component (A), component (C) is preferably liquid at 25°C, and preferably has a viscosity at 25°C measured with a rheometer in the range of 0.01 to 50 Pa·s. The upper limit of the viscosity is more preferably 25 Pa·s, even more preferably 5 Pa·s, and most preferably 3 Pa·s. By making the viscosity of component (C) at 25°C 50 Pa·s or less, component (B) can be efficiently dispersed without impairing compatibility with component (A). Here, the viscosity of component (C) refers to the complex viscosity measured using an Anton Paar rheometer "Physica MCR501" with 25φ parallel plates, a gap of 1 mm, an oscillation mode, an oscillation angle φ=0.0025 rad, a frequency of 1 Hz, and at 25°C.
[0033] The weight average molecular weight of component (C) is preferably in the range of 150 to 100,000. The upper limit of the weight average molecular weight is more preferably 50,000, and even more preferably 10,000. By making the weight average molecular weight 100,000 or less, it is possible to improve compatibility with component (A). In addition, by making the weight average molecular weight 150 or more, it is possible to stably adsorb to component (B), and the dispersion effect can be improved.
[0034] Component (C) is not limited to one type of dispersant, and it is also possible to use two or more types of dispersants in combination, such as a surfactant and a high molecular weight dispersant, or a surfactant and an ionic liquid.
[0035] Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric, and a suitable type and amount can be selected and used according to the required properties.
[0036] The anionic surfactant is not particularly limited, and specifically includes fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfates, alkylaryl sulfonates, alkylnaphthalenesulfonates, dialkylsulfonates, dialkylsulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylaryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphate sulfonates, glycerol borate fatty acid esters, polyoxyethylene glycerol fatty acid esters, etc., and specifically includes sodium dodecylbenzenesulfonate, sodium lauric acid sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate, sodium salt of β-naphthalenesulfonic acid formalin condensates, etc. Examples of commercially available anionic surfactants include Lipon LS-250 (manufactured by Lion Corporation).
[0037] Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts. Specific examples include ammonium stearate, stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, dodecyl benzyl triethyl ammonium chloride, tetradecyl dimethyl benzyl ammonium chloride, and distearyl dimethyl ammonium chloride. Examples of commercially available cationic surfactants include "Nissan Cation (registered trademark)" M2-100R (manufactured by NOF Corp.) and Lipocard 2HP flakes (manufactured by Lion Corp.).
[0038] Examples of amphoteric surfactants include aminocarboxylates.
[0039] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, alkyl allyl ethers, and the like. Specific examples include polyoxyethylene lauryl ethers, sorbitan fatty acid esters, polyoxyethylene octyl phenyl ether, and the like.
[0040] The surfactant to be used is not limited to one type, and two or more types of surfactants may be used in combination.
[0041] Specific examples of high molecular weight dispersants include polyurethane, polyacrylate and other polycarboxylate esters, unsaturated polyamides, polycarboxylic acids, polycarboxylate (partial) amine salts, polycarboxylate ammonium salts, polycarboxylate alkylamine salts, polysiloxanes, long-chain polyaminoamide phosphates, hydroxyl-containing polycarboxylate esters, and modified products thereof, polyalkylene polyamines, amides formed by the reaction of poly(lower alkylene imines) with polyesters having free carboxyl groups, and their salts, and other oil-based dispersants, water-soluble resins and water-soluble polymer compounds such as (meth)acrylic acid-styrene copolymers, (meth)acrylic acid-(meth)acrylic acid ester copolymers, styrene-maleic acid copolymers, polyvinyl alcohol, and polyvinylpyrrolidone, polyester resins, modified polyacrylate resins, ethylene oxide / propylene oxide adducts, and phosphate resins. These can be used alone or in a mixture of two or more, but are not necessarily limited to these.
[0042] Commercially available high molecular weight dispersants include DISPERBYK-101, 103, 107, 108, 110, 111, 116, 130, 140, 154, 161, 162, 163, 164, 165, 166, 170, 171, 174, 180, 181, 182, 183, 184, 185, 190, 2000, 2001, 2020, 2025, 2050, 2070, 2095, 2150, 2155 or Anti-Terra-U, 203, 204, or BYK-P104, P104S, P9920, 220S, 6919, 9076, 9077 or Lactimon, Lactimon-WS or Bykumen (manufactured by Byk-Chemie), SOLSPERSE-3000, 9000, 13000, 13240, 13650, 13940, 16000, 17000, 18000, 20000, 21000, 24000, 26000, 27000, 28000, 31845, 32000, 32500, 32550, 33500, 32600, 34750, 35100, 36600, 38500, 41000, 41090, 53095, 55000, 76500 (Japan Lubrizol Corporation), EFKA-46, 47, 48, 452, 4008, 4009, 4010, 4015, 4020, 4047, 4050, 4055, 4060, 4080, 4400, 4401, 4402, 4403, 4406, 4408, 4300, 4310, 4320, 4330, 4340, 450, 451, 453, 4540, 4550, 4560, 4800, 5010, 5065, 5066, 5070, 7500, 7554, 1101, 120, 150, 1501, 1502, 1503 (Ciba Japan ), "Ajisper (registered trademark)" PA111, PB711, PB821, PB822, PB824 (manufactured by Ajinomoto Fine-Techno Co., Ltd.), "Filanol (registered trademark)" PA-075F, PA-085C, PA-107P or "S-ream (registered trademark)" AD-3172M, AD-374M, AD-508E (manufactured by NOF Corp.), "Hypermer (registered trademark)" KD-1, KD-2, KD-3 (manufactured by Croda), "Phospholan (registered trademark)" PS-131, PS-220, PS-222, PS-236 (manufactured by Akzo Nobel), and the like.
[0043] The ionic liquid may be an organic compound salt such as an imidazolium salt, a pyridinium salt, an ammonium salt, or a phosphonium salt, which is liquid at room temperature.
[0044] Examples of the ionic liquid that is an imidazolium salt include 1,3-dimethylimidazolium methyl sulfate, 1-ethyl-3-methylimidazolium bis(pentafluoroethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoroethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium hexafluorophosphate ... Chiliimidazolium chloride, 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tosylate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-n-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide Methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium 2-(2-methoxyethoxy)ethyl sulfate, 1-butyl-3-methylimidazolium methyl sulfate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-hexyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium hexafluorophosphate, 1-hexyl-3-methylimidazolium chloride 1-Methyl-3-octylimidazolium tetrafluoroborate, 1-methyl-3-octylimidazolium chloride, 1-methyl-3-octylimidazolium tetrafluoroborate, 1,2-dimethyl-3-propyloctylimidazolium tris(trifluoromethylsulfonyl)methide, 1-butyl-2,3-dimethylimidazolium chloride, 1-butyl-2,3-dimethylimidazolium hexafluorophosphate, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate, 1-methyl-3-(3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl)imidazolium hexafluorophosphate, and 1-butyl-3-(3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl)imidazolium hexafluorophosphate.
[0045] Examples of ionic liquids that are pyridinium salts include 3-methyl-1-propylpyridinium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide, 1-propyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium chloride, 1-butyl-4-methylpyridinium hexafluorophosphate, and 1-butyl-4-methylpyridinium tetrafluoroborate.
[0046] Examples of ammonium salt ionic liquids include tetrabutylammonium heptadecafluorooctanesulfonate, tetrabutylammonium nonafluorobutanesulfonate, tetrapentylammonium methanesulfonate, tetrapentylammonium thiocyanate, and methyl-tri-n-butylammonium methylsulfate.
[0047] Examples of ionic liquids that are phosphonium salts include tetrabutylphosphonium methanesulfonate, tetrabutylphosphonium p-toluenesulfonate, trihexyltetradecylphosphonium bis(trifluoroethylsulfonyl)imide, trihexyltetradecylphosphonium bis(2,4,4-trimethylpentyl)phosphinate, trihexyltetradecylphosphonium bromide, trihexyltetradecylphosphonium chloride, trihexyltetradecylphosphonium decanoate, trihexyltetradecylphosphonium hexafluorophosphinate, triethyltetradecylphosphonium tetrafluoroborate, and tributylmethylphosphonium tosylate. These can be used alone or in combination of two or more, but are not necessarily limited to these.
[0048] As the ionic liquid, commercially available products can be used as they are, and examples thereof include 3M (trademark) ionic liquid type antistatic agent FC4400 (manufactured by 3M Japan Ltd.), CIL-313, CIL-312 (all manufactured by Nippon Carlit Co., Ltd.), IL-A2, IL-A5, IL-A12, IL-AP1, IL-AP3, IL-C1, IL-C3, IL-C5, IL-C6, IL-IM1, IL-IM4, IL-MA1, IL-MA2, IL-MA3, IL-P14, IL-P18, IL-OH9 (all manufactured by Koei Chemical Industry Co., Ltd.).
[0049] From the viewpoint of heat resistance and mechanical properties, the content of component (C) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and even more preferably 1 to 3 parts by mass, relative to 100 parts by mass of component (A). When the content of component (C) is 0.1 parts by mass or more, component (B) can be dispersed more efficiently. When the content of component (C) is 10 parts by mass or less, the epoxy resin cured product obtained by curing the epoxy resin composition tends to have higher heat resistance.
[0050] From the viewpoint of easily maintaining the mechanical properties of the fiber reinforced composite material of the present application, the total content of (A) to (C) in the entire epoxy resin composition is preferably 30 to 95 mass%, more preferably 50 to 85 mass%, and even more preferably 60 to 80 mass%. If the total content of (A) to (C) is 30 mass% or more, the mechanical properties are further improved. If it is 95 mass% or less, it is easy to obtain a sufficient effect of improving bending strength.
[0051] From the viewpoint of efficiently dispersing component (B) in component (A), component (C) is compatible when mixed with component (A). When 2 parts by mass of component (C) are mixed with 100 parts by mass of component (A) at room temperature, i.e., 25°C, the compatible state is when the area ratio of the phase formed by component (C) to the total area of the observed image of the mixture is 0 to 1.5%. The area ratio of the phase formed by component (C) is preferably 0 to 1%, more preferably 0 to 0.7%. By making the area ratio of the phase formed by component (C) 1.5% or less, it becomes possible for component (C) to be uniformly present in component (A), and the dispersion effect can be efficiently expressed. In the present invention, the compatibility of component (C) with component (A) is evaluated by the method described below.
[0052] The epoxy resin composition of the present invention has a viscosity of 0.1 to 100 Pa·s at 25°C. The upper limit of the viscosity is preferably 50 Pa·s, more preferably 25 Pa·s, and even more preferably 20 Pa·s. By making the viscosity at 25°C 0.1 Pa·s or more, the viscosity during impregnation of the epoxy resin composition does not become too low, and the epoxy resin composition does not flow out to the outside, and it is easy to impregnate the reinforcing fiber uniformly. In addition, by making the viscosity at 25°C 100 Pa·s or less, it is possible to suppress the decrease in impregnation property and suppress the generation of voids when it is made into a carbon fiber reinforced composite material. The viscosity is measured for the epoxy resin composition after mixing each component and stirring for 1 minute. In the present invention, the viscosity of the epoxy resin composition is measured by the method described later. As a means for satisfying the above viscosity range, for example, the content of solid components in the epoxy resin composition is reduced, or a component (A) with a lower viscosity is used.
[0053] The degree of dispersion of component (B) in component (A) is 0.1 to 0.8, preferably 0.1 to 0.7, and more preferably 0.1 to 0.5. By making the degree of dispersion of component (B) 0.1 or more, the effect of component (B) can be efficiently expressed. By making the degree of dispersion of component (B) 0.8 or less, component (B) can be uniformly dispersed, so that a molding material for a fiber-reinforced composite material having improved impregnation into reinforcing fibers, less unevenness in physical properties after curing, and good appearance quality can be obtained. In the present invention, the degree of dispersion of component (B) is measured by the method described later. As a means for making the degree of dispersion of component (B) in component (A) within the above range, for example, a solid curing agent having a lower surface tension can be used as component (B).
[0054] From the viewpoint of suppressing gas generation, the epoxy resin composition of the present invention preferably has a large amount of non-volatile components. Specifically, it is preferably 95% by mass or more, more preferably 97% by mass or more, even more preferably 98% by mass or more, and most preferably 98.5% by mass or more. The upper limit is about 100% by mass.
[0055] The term "non-volatile components" used here refers to the percentage of remaining components after 24 hours of vacuum drying at 25°C and a gauge pressure of -0.1 MPa. Here, the gauge pressure refers to the pressure when atmospheric pressure is set to zero, and the lower the pressure, the higher the degree of vacuum and the greater the ability to remove volatile components.
[0056] The heat resistance of the fiber-reinforced composite material using the epoxy resin composition of the present invention depends on the glass transition temperature (Tg) of the epoxy resin cured product obtained by curing the epoxy resin composition. In order to obtain a fiber-reinforced composite material having high heat resistance, the glass transition temperature of the epoxy resin cured product at a degree of cure of 85 to 95% (for example, 90%) is 110°C or higher. As a means for setting the glass transition temperature within the above range, for example, the epoxy resin composition may contain more rigid molecular structures such as aromatic groups to increase the glass transition temperature. As an example of the curing conditions of the epoxy resin composition, for example, heating at a temperature of 180°C for 3 hours may be mentioned. In the present invention, the degree of cure of the epoxy resin cured product is determined by the method described below.
[0057] The upper limit of the glass transition temperature is not particularly limited, but is preferably 250°C or less. It is more preferable that the glass transition temperature is 120°C or more and 220°C or less. If the glass transition temperature is 110°C or more, high heat resistance is easily imparted to the epoxy resin cured product obtained by curing the epoxy resin composition. If the glass transition temperature is 250°C or less, the crosslink density of the three-dimensional crosslinking structure of the epoxy resin cured product obtained by curing the epoxy resin composition is not too high, and high mechanical properties are easily expressed. Here, the glass transition temperature of the epoxy resin cured product obtained by curing the epoxy resin composition is determined by measurement using a dynamic viscoelasticity measuring device (DMA). That is, a rectangular test piece cut out from a resin cured plate is used to perform DMA measurement at an elevated temperature, and the temperature at the inflection point of the obtained storage modulus G' is defined as Tg. The measurement conditions are as described in the examples.
[0058] The molding material for fiber-reinforced composite materials of the present invention is a molding material for fiber-reinforced composite materials comprising a thickened resin and reinforcing fibers, and the thickened resin is the epoxy resin composition of the present invention in a semi-cured state. The definition of the thickened resin will be described later.
[0059] In the molding material for fiber-reinforced composite materials of the present invention, the dispersity of component (B) in the thickened resin is preferably 0.1 to 1.0, more preferably 0.1 to 0.9, even more preferably 0.1 to 0.8, and most preferably 0.1 to 0.7. By making the dispersity of component (B) 0.1 or more, the effect of component (B) as a curing agent can be efficiently exhibited. By making the dispersity of component (B) 1.0 or less, a molding material for fiber-reinforced composite materials with less unevenness in physical properties after curing and good appearance quality can be obtained. In the present invention, the dispersity of component (B) is measured by the method described below. As a means for achieving the dispersity of component (B) in the thickened resin in the molding material for fiber-reinforced composite materials in the above range, for example, the epoxy resin composition of the present invention is used, and in particular, in the epoxy resin composition before being impregnated into reinforcing fibers, the dispersity of component (B) in component (A) is set to the above range.
[0060] The molding material for fiber-reinforced composite materials of the present invention is excellent in that it has excellent dispersibility of the solid curing agent in the epoxy resin composition and excellent impregnation into the reinforcing fibers, and therefore has little unevenness in physical properties after curing and gives a fiber-reinforced composite material with excellent mechanical properties. The unevenness in physical properties of the fiber-reinforced composite material of the present invention is preferably such that the variation in bending strength (CV value) is 15% or less, more preferably 10% or less.
[0061] Here, the CV value of bending strength is calculated by calculating the average bending strength from 10 randomly selected test pieces, dividing the difference between this average value and the bending strength of each test piece by the average value, and converting the result into a percentage and averaging the result.
[0062] In the molding material for fiber-reinforced composite material of the present invention, the type and length of the reinforcing fiber, the content ratio of the reinforcing fiber and the resin, etc. are not particularly limited, but examples thereof include glass fiber, carbon fiber, graphite fiber, aramid fiber, boron fiber, alumina fiber, and silicon carbide fiber. Two or more of these reinforcing fibers may be mixed and used. In order to obtain a lighter and more durable molded product, it is preferable to use carbon fiber or graphite fiber. In particular, in applications where there is a high demand for lighter materials and higher strength, it is preferable that the reinforcing fiber is carbon fiber because of its excellent specific elastic modulus and specific strength. As the carbon fiber, any kind of carbon fiber can be used depending on the application, but from the viewpoint of impact resistance, it is preferable that the carbon fiber has a tensile elastic modulus of at most 400 GPa. In addition, from the viewpoint of strength, a composite material having high rigidity and mechanical strength is obtained, so that a carbon fiber having a tensile strength of preferably 4.4 to 6.5 GPa is used. In addition, tensile elongation is also an important factor, and a high-strength and high-elongation carbon fiber of 1.7 to 2.3% is preferable. Therefore, carbon fibers having a tensile modulus of at least 230 GPa, a tensile strength of at least 4.4 GPa, and a tensile elongation of at least 1.7% are most suitable.
[0063] Examples of commercially available carbon fibers include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T700S-12K (all manufactured by Toray Industries, Inc.).
[0064] The reinforcing fibers used in the present invention may be either continuous or discontinuous fibers.
[0065] When the reinforcing fiber is a continuous fiber, examples of the form of the reinforcing fiber include long fibers aligned in one direction, tows, woven fabrics, mats, knits, braids, and other fiber structures. When the reinforcing fiber is a continuous fiber, a reinforcing fiber having an average fiber diameter of 3 μm to 12 μm and a reinforcing fiber mass fraction in the range of 40% to 90% is preferably used. If the reinforcing fiber mass fraction is 40% or more, the mass of the obtained fiber-reinforced composite material is not excessive, and the advantages of the fiber-reinforced composite material having excellent specific strength and specific elastic modulus can be fully exhibited, and if the reinforcing fiber mass fraction is 90% or less, the impregnation of the epoxy resin composition into the reinforcing fiber is excellent. Examples of fiber-reinforced composite materials obtained using such continuous fibers include prepregs and towpregs.
[0066] When the reinforcing fibers are discontinuous fibers, the reinforcing fibers are preferably used with a fiber length of 5 mm to 100 mm, an average fiber diameter of 3 μm to 12 μm, and a reinforcing fiber mass fraction of 40% to 90%. If the reinforcing fiber mass fraction is 40% or more, the mass of the obtained fiber-reinforced composite material is not excessive, and the advantages of the fiber-reinforced composite material having excellent specific strength and specific elastic modulus can be fully exhibited, and if the reinforcing fiber mass fraction is 90% or less, the impregnation of the epoxy resin composition into the reinforcing fiber is excellent. Examples of molding materials for fiber-reinforced composite materials obtained using such discontinuous fibers include BMC and SMC. Among these, SMC is particularly preferably used from the viewpoints of productivity and freedom of shape of the molded body.
[0067] The form of the bundle of discontinuous fibers is not particularly limited, and known techniques can be applied. In the plane of the bundle of fibers where the width in the direction perpendicular to the arranging direction of the reinforcing fibers is maximum, the acute angles formed by the sides of the arrangement of the ends of the reinforcing fibers in the bundle of fibers with respect to the arranging direction of the reinforcing fibers are angle a and angle b, respectively. It is preferable that the angles a and b are 2° or more and 30° or less. The smaller the angles a and b of the sides formed by the arrangement of the ends of the reinforcing fibers in the bundle of fibers with respect to the arranging direction of the reinforcing fibers, the higher the homogeneity of the bundle of fibers and the resin becomes, so that the fiber-reinforced composite material molded using the bundle of fibers has a large effect of improving the surface quality and strength. When the angles a and b are 30° or less, the effect is remarkable. However, on the other hand, the smaller the angles a and b are, the lower the handleability of the bundle of fibers themselves becomes. In addition, the smaller the angle between the arranging direction of the reinforcing fibers and the cutting blade, the lower the stability in the cutting process. Therefore, the angles a and b are preferably 2° or more. The angles a and b are more preferably 3° or more and 25° or less. In view of the balance between the surface quality and strength improvement effect of the fiber-reinforced composite material and the processability in the manufacturing process of the bundle-shaped assembly, the angles a and b are even more preferably 5° or more and 15° or less.
[0068] Examples of cutting means for the continuous reinforcing fiber bundle for producing a bundle-like aggregate of discontinuous fibers include rotary cutters such as a guillotine cutter, a roving cutter, etc. The continuous reinforcing fiber bundle is inserted into the cutting means and cut in a state in which the longitudinal direction of the continuous reinforcing fiber bundle and the direction of the cutting blade equipped on the cutting means are relatively oblique.
[0069] The method for producing the molding material for fiber-reinforced composite material of the present invention is not particularly limited. For example, the epoxy resin composition of the present invention is impregnated into reinforcing fibers in the presence of component (D): a compound that undergoes a thickening reaction with an epoxy resin (hereinafter, sometimes simply referred to as component (D)) by a known method suited to the shape of the reinforcing fibers, and then the epoxy resin composition is kept at a temperature of about room temperature to about 80°C for several hours to several days to reach a semi-cured state where the viscosity increase of the epoxy resin composition is saturated, thereby obtaining the molding material for fiber-reinforced composite material of the present invention. Here, the epoxy resin composition in which the viscosity increase is saturated and the semi-cured state is reached is called a thickened resin. The thickening reaction refers to the epoxy resin composition being in a semi-cured state. In the present invention, the thickening condition is adopted in which the epoxy resin composition is kept at 40°C for 24 hours to saturate the viscosity increase of the resin composition and reach a semi-cured state. Component (D) is not particularly limited as long as it is a component that thickens the epoxy resin composition by covalently bonding with the epoxy resin, but it is preferably an aliphatic amine, an acid anhydride, an isocyanate compound, or a derivative thereof.
[0070] The aliphatic amine is an amine having no aromatic ring, and is not particularly limited as long as it has one or more amino groups in the molecule, but specific examples include polyalkylene polyamine, isophorone diamine, 3,3'-dimethyl di(cyclohexylamine), 4,4'-diaminodicyclohexylmethane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 3,3'-diethyl-4,4'-diaminodicyclohexylmethane, n-aminoethylpiperazine, norbornane diamine, diethylene glycol diaminopropyl ether, adipic acid dihydrazide, hydrazine, cyanamide, and derivatives thereof. The amino group is preferably bonded to a primary, secondary, or tertiary carbon atom, and more preferably to a primary or secondary carbon atom in order to easily thicken the epoxy resin composition.
[0071] An acid anhydride is a compound having one or more acid anhydride groups in the molecule. Examples of acid anhydrides include methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, maleic anhydride, and succinic anhydride.
[0072] The isocyanate compound is not particularly limited as long as it has one or more isocyanate groups on average in one molecule, and examples thereof include aliphatic isocyanates, aromatic isocyanates, etc. Examples of the aliphatic isocyanates include ethylene diisocyanate, trimethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, propylene-1,2-diisocyanate, 2,3-dimethyltetramethylene diisocyanate, butylene-1,2-diisocyanate, butylene-1,3-diisocyanate, 1,4-diisocyanate hexane, cyclopentene-1,3-diisocyanate, isophorone diisocyanate, 1,2,3,4-tetraisocyanate butane, butane-1,2,3-triisocyanate, etc. Examples of aromatic isocyanates include p-phenylene diisocyanate, 1-methylphenylene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, tolylene diisocyanate, diphenyl-4,4-diisocyanate, benzene-1,2,4-triisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate (MDI), diphenylpropane diisocyanate, tetramethylene xylene diisocyanate, polymethylene polyphenyl polyisocyanate, and those having a structure in which these aromatic isocyanates are linked via methylene groups or the like.
[0073] In the present invention, the viscosity of component (D) at 25° C. is preferably from 1 mPa·s to 10,000 mPa·s, and more preferably from 10 mPa·s to 10,000 mPa·s. When the viscosity of component (D) is in the above range, the viscosity of the epoxy resin composition is easily reduced sufficiently.
[0074] The fiber-reinforced composite material of the present invention is obtained by molding the molding material for fiber-reinforced composite material of the present invention.
[0075] The method for producing the fiber-reinforced composite material of the present invention is not particularly limited, but the hand lay-up method, the filament winding method, the pultrusion method, the resin transfer molding (RTM) method, the autoclave molding method of prepreg, and further, the press molding method of molding materials for fiber-reinforced composite materials such as prepreg, towpreg, bulk molding compound (BMC), sheet molding compound (SMC), etc. are preferably used.
[0076] Fiber-reinforced composite materials, particularly those used in the automotive field, are required to have high heat resistance and mechanical properties such as bending strength. The fiber-reinforced composite material of the present invention is excellent in heat resistance and mechanical properties, and is therefore suitable for use in the automotive field. In addition, the molding material for fiber-reinforced composite material of the present invention does not allow the resin to flow first during press molding, and exhibits excellent fluidity regardless of the molding temperature, resulting in a fiber-reinforced composite material with extremely high homogeneity between the fiber and the resin. EXAMPLES
[0077] The epoxy resin composition, molding material for fiber-reinforced composite material, and fiber-reinforced composite material of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0078] <Resin raw materials> The following resin raw materials were used to obtain the epoxy resin compositions of the Examples and Comparative Examples. The numerical values of each component in the column for the epoxy resin composition in the tables indicate the content, and the unit ("parts") is "parts by mass" unless otherwise specified.
[0079] 1. Component (A): Epoxy resin with two or more epoxy groups in one molecule "jER (registered trademark)" 828 (manufactured by Mitsubishi Chemical Corporation): liquid bisphenol A type epoxy resin. "jER (registered trademark)" 154 (manufactured by Mitsubishi Chemical Corporation): Phenol novolac type solid epoxy resin. "Epototo (registered trademark)" YD-128S (manufactured by Nippon Steel Chemical & Material Co., Ltd.) "Denacol (registered trademark)" EX-411 (manufactured by Nagase ChemteX Corporation). "Denacol (registered trademark)" EX-614 (manufactured by Nagase ChemteX Corporation): sorbitol polyglycidyl ether.
[0080] 2. Component (B): Solid hardener "jER Cure (registered trademark)" DICY7 (average particle size: 3 μm) (manufactured by Mitsubishi Chemical Corporation): dicyandiamide. "jER Cure (registered trademark)" DICY50 (average particle size: 45 μm) (manufactured by Mitsubishi Chemical Corporation) "DYHARD (registered trademark)" 100SF (average particle size: 1.5 μm) (manufactured by AlzChem) "Amicure (registered trademark)" Cg-325G (average particle size: 15 μm) (manufactured by EVONIK).
[0081] 3. Component (C): A dispersant compatible with component (A). "3M (registered trademark)" ionic liquid type antistatic agent FC4400 (manufactured by 3M Japan Ltd.) "Nissan Cation (registered trademark)" M2-100R (manufactured by NOF Corporation) CIL-312 (manufactured by Nippon Carlit Co., Ltd.) Lipocard 2HP flakes (manufactured by Lion Corporation) Lipon LS-250 (manufactured by Lion Corporation) ·IL-A2 (manufactured by Koei Chemical Industry Co., Ltd.) IL-OH9 (manufactured by Koei Chemical Industry Co., Ltd.) Ammonium stearate (Nacalai Tesque, Inc.) Ammonium salts not falling under component (C) Ammonium benzoate (manufactured by Toyama Pharmaceutical Co., Ltd.).
[0082] 4. Component (D): Compound that reacts with epoxy resin to thicken 1,4-Butanediamine (Tokyo Chemical Industry Co., Ltd.) · “Lupranate (registered trademark)” M20S (manufactured by BASF INOAC Polyurethanes Co., Ltd.): polymeric MDI (polymethylene polyphenyl polyisocyanate).
[0083] <Evaluation of compatibility of component (C) with component (A)> A mixture of 100 parts by mass of component (A) and 2 parts by mass of component (C) was mixed at room temperature (25°C) to prepare a mixture of components (A) and (C). 0.5 mg of the mixture of components (A) and (C) was applied to a cover glass placed on a slide glass, and the cover glass was placed on top of the cover glass. The epoxy resin composition was pressed and spread from the top of the cover glass, and observed using a Nikon optical microscope "OPTIPHOT" and a Zeiss camera "AxioCam MRc" to obtain a dispersion image. The particles of component (C) were extracted from the obtained dispersion image using Media Cybernetics' image processing software "Image Pro Premier 3D", and the area of the phase formed by component (C) / the area of the entire observed image x 100 was calculated.
[0084] <Preparation of Epoxy Resin Composition> Each component was mixed in the amounts shown in Tables 1-1, 1-2, and 2 to prepare an epoxy resin composition.
[0085] <Preparation of epoxy resin composition for fiber reinforced composite material (SMC)> The components were mixed in the amounts shown in Table 3 to prepare epoxy resin compositions.
[0086] <Measurement of Viscosity of Epoxy Resin Composition Immediately After Preparation> The complex viscosity of the epoxy resin compositions prepared in the above <Preparation of epoxy resin composition> and <Preparation of epoxy resin composition for molding compound for fiber reinforced composite material (SMC)> was measured using an Anton Paar rheometer "Physica MCR501" with 25φ parallel plates at a gap of 1 mm, in vibration mode, with an oscillation angle φ=0.0025 rad, at a frequency of 1 Hz, and at 25°C.
[0087] <Measurement of the degree of dispersion of component (B) in component (A)> 0.5 mg of the epoxy resin composition prepared in the above <Preparation of epoxy resin composition> and <Preparation of epoxy resin composition for molding material for fiber reinforced composite material (SMC)> was applied to a cover glass placed on a slide glass, and the cover glass was placed on top of the epoxy resin composition, which was then pressed and spread over the cover glass. A dispersion image was obtained by observing the image at a magnification of 200x using a Nikon optical microscope "OPTIPHOT" and a Zeiss camera "AxioCam MRc". The particles of component (B) were extracted from the obtained dispersion image using Media Cybernetics' image processing software "Image Pro Premier 3D", and the average area and standard deviation of the Voronoi division area for the particles of component (B) were calculated, and the standard deviation was divided by the average area to obtain the degree of dispersion.
[0088] <Impregnation evaluation> 2 mg of carbon fiber having a length of 3 mm and an average fiber diameter of 7 μm was inserted into the nozzle of a 1 mL syringe "SS-01T" manufactured by Terumo and pushed down to the 0.1 mL mark with the plunger. After the plunger was removed, 0.6 mL of the epoxy resin composition prepared in the above <Preparation of epoxy resin composition> and <Preparation of epoxy resin composition for fiber reinforced composite molding compound (SMC)> was dropped from the nozzle and the time from when the resin reached the 0.1 mL mark to when it reached the tip of the syringe was measured.
[0089] <Preparation of cured epoxy resin> The epoxy resin composition prepared in <Preparation of the Epoxy Resin Composition> and <Preparation of the Epoxy Resin Composition for Molding Materials (SMC) for Fiber Reinforced Composite Materials> was degassed in vacuo and then poured into a mold set to a thickness of 2 mm by a 2-mm-thick spacer made of "Teflon (registered trademark)". It was cured at a temperature of 180 °C for 3 hours to obtain an epoxy resin cured product with a thickness of 2 mm.
[0090] <Measurement of Degree of Curing> 5 mg of the epoxy resin cured product obtained in <Preparation of the Epoxy Resin Cured Product> above was sampled, and using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments), the temperature was raised from 30 °C to 350 °C at a heating rate of 10 °C / min for measurement to obtain an exothermic curve, and by integrating the exothermic peak thereof, the total exotherm QT of the thermosetting resin and the residual exotherm QR of the epoxy resin cured product were calculated. When peaks of exotherm or endotherm due to decomposition reaction or the like were observed, the measurement was carried out in the temperature range below those peaks. Here, the degree of curing (%) obtained by DSC was determined by degree of curing (%) = (QT - QR) / QT × 100.
[0091] <Measurement of Glass Transition Temperature Tg of Epoxy Resin Cured Product> From the epoxy resin cured product having the degree of curing measured in <Measurement of Degree of Curing> above obtained in <Preparation of the Epoxy Resin Cured Product> above, a test piece with a width of 12.7 mm and a length of 40 mm was cut out, and Tg measurement was carried out using DMA (ARES manufactured by TA Instruments). The measurement conditions were a heating rate of 5 °C / min. The temperature at the inflection point of the storage modulus G' obtained by the measurement was taken as Tg.
[0092] <Preparation of SMC> As the carbon fiber, "Torayca (registered trademark)" T700S-12K (manufactured by Toray Industries, Inc.) was used. By cutting the continuous carbon fiber strand at a desired angle and spraying it so as to uniformly disperse the bundle-like aggregate of carbon fibers, a discontinuous carbon fiber nonwoven fabric with an isotropic fiber orientation was obtained. A rotary cutter was used as the cutting device. The blade interval was 30 mm. Also, the basis weight of the discontinuous carbon fiber nonwoven fabric was 1 kg / m 2It was. The discontinuous carbon fiber nonwoven fabric was sandwiched between polyethylene films coated with the epoxy resin composition obtained in <Preparation of Epoxy Resin Composition for Molding Material (SMC) for Fiber Reinforced Composite Material>, so that the carbon fiber weight content of the resulting SMC was 40%, and pressed with a roller to impregnate the epoxy resin composition, thereby obtaining a sheet-shaped SMC precursor. This SMC precursor was held at 40 °C for 24 hours to thicken the resin, thereby obtaining SMC.
[0093] <Measurement of Dispersion Degree of Component (B) in Resin after Thickening of Molding Material for Fiber Reinforced Composite Material> Regarding the epoxy resin composition portion on the surface of the SMC obtained in <Production of SMC> above, an image obtained by observing at a magnification of 1000 times using a digital microscope VHX-7000 (manufactured by Keyence Corporation) was used to extract the particles of component (B) with image analysis software Image Pro Premier 3D (manufactured by Media Cybernetics, Inc.). The average area and its standard deviation of the region obtained by Voronoi division of the particles of component (B) were calculated, and the value obtained by dividing the standard deviation by the average area was defined as the dispersion degree.
[0094] <SMC Impregnation Evaluation> The SMC obtained in <Production of SMC> above was split into two pieces with the front and back surfaces, and when the resin was impregnated up to the center part in the thickness direction, the impregnation property was defined as good, and when not impregnated, the impregnation property was defined as poor.
[0095] <Appearance Quality Evaluation of Fiber Reinforced Composite Material> Using the above SMC, it was cured under a pressure of 10 MPa for 30 minutes at 150 °C using a compression press to obtain a flat plate-shaped fiber reinforced composite material with dimensions of 300 × 400 mm and a thickness of 1.6 mm. The surface of the obtained fiber reinforced composite material was evenly divided into 9 parts, and the glossiness at each point was measured at an incident angle of 60° using a digital variable angle gloss meter UGV-5D (manufactured by Suga Test Instruments Co., Ltd.). The average value of each point was calculated, and the difference between this average value and the glossiness at each point was divided by the average value and converted to a percentage, and the CV value was calculated from the averaged value. Those with a CV value of less than 5% were defined as good, and those with a CV value of 5% or more were defined as poor.
[0096] <Measurement of Bending Strength of Fiber Reinforced Composite Material for SMC> Five test pieces (10 pieces in total) of 100×25×1.6 mm were cut out from the flat plate-shaped fiber reinforced composite material obtained as described above at 0 degrees (0 degrees in the longitudinal direction of the flat plate) and 90 degrees, respectively, and the measurement was carried out in accordance with JIS K7074 (1988).
[0097] (Examples 1 - 8) The type of component (C) was changed, and the resin composition was prepared according to the above-described method for preparing the resin composition with the contents described in Table 1-1. The viscosity, dispersity, and impregnability of the epoxy resin composition immediately after preparation were measured. Also, epoxy resin cured products of the respective epoxy resin compositions were prepared. The viscosity at 25°C of the epoxy resin composition immediately after preparation was in the range of 0.1 to 100 Pa·s. Also, the dispersity of component (B) in component (A) was in the range of 0.1 to 0.8. The impregnation time became shorter compared to Comparative Example 1 in which component (C) was not added, and an improvement in impregnability was confirmed.
[0098] (Examples 11 - 16) The same procedure as in Example 1 was carried out except that the types and contents of component (B) and component (C) were changed. The viscosity, dispersity, and impregnability of the epoxy resin composition immediately after preparation were measured. Also, epoxy resin cured products of the respective epoxy resin compositions were prepared. The viscosity at 25°C of the epoxy resin composition immediately after preparation was in the range of 0.1 to 100 Pa·s. Also, the dispersity of component (B) in component (A) was in the range of 0.1 to 0.8. The impregnation time became shorter compared to Comparative Example 1 in which component (C) was not added, and an improvement in impregnability was confirmed.
[0099] (Comparative Example 1) Resin compositions were prepared according to the above-mentioned resin composition preparation method using the contents of components (A) and (B) shown in Table 2, and the viscosity and impregnation properties of the epoxy resin compositions immediately after preparation were measured. In addition, epoxy resin cured products were prepared from each epoxy resin composition. The viscosity of the epoxy resin compositions immediately after preparation at 25°C was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was 1.0, and the impregnation time was 680 seconds, indicating poor impregnation properties.
[0100] Example 9 The same procedure as in Example 1 was repeated except that the content of component (B) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was within the range of 0.1 to 0.8. The impregnation time was shorter than that of Comparative Example 3 in which component (C) was not added, and improvement in impregnation was confirmed.
[0101] Example 10 The same procedure as in Example 9 was repeated except that the type and content of component (A) were changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was within the range of 0.1 to 0.8. The impregnation time was shorter than that of Comparative Example 3 in which component (C) was not added, and improvement in impregnation was confirmed.
[0102] Comparative Example 3 The same procedure as in Example 9 was repeated except for omitting component (C). The viscosity of the epoxy resin composition at 25°C immediately after preparation was in the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was 1.0, and the impregnation time was 564 seconds, which showed inferior impregnation properties compared to Examples 9 and 10.
[0103] (Example 17) The same procedures as in Example 1 were carried out except that the content of component (B) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was within the range of 0.1 to 0.8. The impregnation time was shorter than that of Comparative Example 5, in which component (C) was not added, and improvement in impregnation was confirmed.
[0104] Comparative Example 5 The same procedures as in Example 17 were carried out except for omitting component (C). The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was 1.3, and the impregnation time was 823 seconds, which showed inferior impregnation properties compared to Example 17.
[0105] Comparative Example 2 The same procedure as in Example 1 was carried out except that the type of component (C) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100. In addition, the dispersity of component (B) in component (A) was 1.2, and the impregnation time was 1070 seconds, indicating poor impregnation properties.
[0106] Comparative Example 4 The same procedure as in Example 1 was repeated except that the type of component (A) and the content of component (B) were changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was higher than 100 Pa s. In addition, the dispersity of component (B) in component (A) was 0.8, and the impregnation time was 2951 seconds, indicating poor impregnation.
[0107] Comparative Example 6 The same procedure as in Example 1 was repeated except that the content of component (B) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was higher than 100 Pa s. In addition, the dispersity of component (B) in component (A) was 1.4, and the impregnation time was 4100 seconds, indicating poor impregnation.
[0108] Comparative Example 7 The same procedure as in Example 1 was repeated except that the content of component (C) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The dispersity of component (B) in component (A) was 1.2, and the impregnation time was 930 seconds, indicating poor impregnation properties.
[0109] (Examples 18 and 19) The type of component (C) was changed, and epoxy resin compositions were prepared according to the above-mentioned method for preparing epoxy resin compositions for SMC, with the content shown in Table 3, and the viscosity, dispersibility, and impregnation of the epoxy resin compositions immediately after preparation were measured. In addition, epoxy resin cured products were prepared from each epoxy resin composition. The viscosity of the epoxy resin composition immediately after preparation at 25°C was in the range of 0.1 to 100 Pa·s. In addition, the dispersibility of component (B) in component (A) was in the range of 0.1 to 0.8. The impregnation time was shorter than that of Comparative Example 8 in which component (C) was not added, and improvement in impregnation was confirmed. In addition, each SMC was prepared, and the dispersibility and SMC impregnation of component (B) in the resin after thickening of the molding material for fiber reinforced composite materials were evaluated. The dispersibility was in the range of 0.1 to 1.0, and the SMC impregnation and appearance quality were good.
[0110] Comparative Example 8 The same procedures as in Examples 18 and 19 were carried out except for omitting component (C). The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The degree of dispersion of component (B) in component (A) was 1.1, and the impregnation time was 421 seconds, which showed poor impregnation properties compared to Examples 9 and 10. The degree of dispersion of component (B) in the resin after thickening of the molding material for fiber-reinforced composite material was 1.1, and the SMC impregnation properties and appearance quality were poor.
[0111] (Example 20) The same procedures were carried out as in Examples 18 and 19, except that the types and contents of components (A) to (D) were changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was in the range of 0.1 to 100 Pa·s. The degree of dispersion of component (B) in component (A) was in the range of 0.1 to 0.8. The impregnation time was shorter than that of Comparative Examples 9 and 10, in which component (C) was not added, and improvement in impregnation was confirmed. In addition, each SMC was prepared, and the degree of dispersion of component (B) in the resin after thickening of the molding material for fiber reinforced composite material was measured. The degree of dispersion was in the range of 0.1 to 1.0, and the SMC impregnation and appearance quality were good.
[0112] Comparative Example 9 The same procedure as in Example 20 was repeated except for omitting component (C). The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The degree of dispersion of component (B) in component (A) was 1.2, and the impregnation time was 540 seconds, which showed poor impregnation compared to Example 20. The degree of dispersion of component (B) in the resin after thickening of the molding material for fiber-reinforced composite material was 1.3, and the SMC impregnation and appearance quality were poor.
[0113] Comparative Example 10 The same procedure as in Example 20 was repeated except that the type of component (C) was changed. The viscosity of the epoxy resin composition at 25°C immediately after preparation was within the range of 0.1 to 100 Pa s. The degree of dispersion of component (B) in component (A) was 1.3, and the impregnation time was 793 seconds, which showed poor impregnation compared to Example 20. The degree of dispersion of component (B) in the resin after thickening of the molding material for fiber-reinforced composite material was 1.5, and the SMC impregnation and appearance quality were poor.
[0114] [Table 1-1]
[0115] [Table 1-2]
[0116] [Table 2]
[0117] [Table 3] [Industrial Applicability]
[0118] The epoxy resin composition of the present invention is superior in dispersibility of the solid curing agent and impregnation into reinforcing fibers compared to conventional epoxy resin compositions, and therefore provides a molding material for fiber-reinforced composite materials with less unevenness in physical properties after curing and good appearance quality, and further, by using such molding material for fiber-reinforced composite materials, fiber-reinforced composite materials with excellent appearance quality and mechanical properties can be obtained. As a result, the composition is suitable for use in fibers for aerospace and automotive applications, as well as sports and industrial applications in general.
Claims
1. An epoxy resin composition comprising all of the following components (A) to (C), wherein the dispersity of component (B) in component (A) is 0.1 to 0.8, the viscosity at 25°C is 0.1 to 100 Pa s, and the glass transition temperature of a cured epoxy resin material at a degree of cure of 85 to 95% is 110°C or higher. Component (A): An epoxy resin having two or more epoxy groups in one molecule. Component (B): Solid hardener Component (C): A dispersant compatible with component (A)
2. 2. The epoxy resin composition according to claim 1, wherein the content of component (C) is 0.1 to 10 parts by mass per 100 parts by mass of component (A).
3. 3. The epoxy resin composition according to claim 1, wherein the average particle size of component (B) is 0.5 to 50 μm.
4. 4. The epoxy resin composition according to claim 1, wherein the content of component (B) is 1 to 50 parts by mass per 100 parts by mass of component (A).
5. The epoxy resin composition according to any one of claims 1 to 4, wherein the non-volatile component is 95 mass% or more.
6. A molding material for a fiber-reinforced composite material comprising a thickened resin and reinforcing fibers, wherein the thickened resin is the epoxy resin composition according to any one of claims 1 to 5 in a semi-cured state.
7. 7. The molding material for fiber-reinforced composite materials according to claim 6, wherein the degree of dispersion of component (B) in the resin after thickening is 0.1 to 1.
0.
8. The molding material for a fiber-reinforced composite material according to claim 6 or 7, wherein the reinforcing fiber is a carbon fiber.
9. A fiber-reinforced composite material obtained by molding the molding material for fiber-reinforced composite materials according to any one of claims 6 to 8.
Citation Information
Patent Citations
Production of impregnating resin composition, prepreg and laminate
JP1990286722A
Epoxy resin composition and method for producing prepreg
JP2002220432A
Method for producing wet prepreg, method for producing composite material, cloth for wet prepreg and wet prepreg and composite material made thereof
JP2003213015A
Method for producing epoxy resin composition
JP2017019977A
Prepreg, prepreg laminate, and fiber-reinforced composite material
WO2018066600A1